Affixation: A Linguistic Strategy For Language Development, - DR. ANIEKAN NYARKS (International Journal on Integrated Education, 2022)
A linguistic strategy for language development aims at the development of a technique which enables the language to develop to a metalanguage. We employed survey and library sources and personal intuition as an Anaang language speaker. The theoretical framework used in this work is the theory of instrumentalism. It was realized that affixation is one of the best techniques of developing Anaang language, as the base accommodates the prefix and suffix comfortably. The elaboration of this technique coupled with other coinage techniques will help the language to achieve standardization.